Natural Killer Cells and Their Activation Status in Normal Pregnancy - Mosimann, Beatrice; Wagner, Marion; Shehata, Hassan; Poon, Leona C. Y.; Ford, Brian; Nicolaides, Kypros H.; Bansal, Amolak S. (International Journal of Reproductive Medicine, 2013)
Increased peripheral blood-activated NK cell counts are associated with increased risk of miscarriage and failed in vitro fertilization treatment. However, assessment of activated peripheral NK cells in normal and pathological pregnancies beyond implantation and early miscarriage has not been described. Total CD69 expressing NK cells counts were measured by flow cytometry in healthy women with singleton pregnancies, including 45 at 11+6–13+6 weeks’ gestation, 46 at 20+0–22+4 weeks, and 42 at 31+6–33+5 weeks. The number of peripheral blood NK cells decreased, whereas the percentage of activated CD69 expressing NK cells increased from the first to the third trimester of pregnancy. This study shows the course of peripheral blood NK cells and activated CD69 expressing NK cells in uncomplicated nulliparous singleton pregnancies. This is a first step in understanding their implication in pathological pregnancies.